Tradução e adaptação transcultural da escala "Smoking Cessation Counseling-SCC" - Zambardi, Juliana Maria Ruoco [UNIFESP] (2016)
Introduction: There are few instruments designed to evaluate smoking cessation practices and adherence to them by health care providers. In view of this deficit, Newhouse et al. created an instrument, the Smoking Cessation Counseling Scale (SCC), which enables evaluation of smoking cessation counseling practices applied in nursing clinical practice. Objective: To translate and culturally adapt the "Smoking Cessation Counseling" scale into Brazilian Portuguese for evaluation of nurse intervention practices in smoking cessation counseling. Method: The adaptation process followed the following stages: translation, synthesis of translations, back-translation, experts committee, pretesting and weighting of the scores. Results: During the translation process, two translationswere obtained, one pure and literal, and the second one towards the study phenomenon. The researcher, by working with the original instrument and the two translations, built a synthesis (T12) of the two translations after discussions with the translators in order to minimize possible errors or additions of words and phrases that could change the direction of the scale items. After synthesizing the translations, two back-translations of the instrument where performed without any difficulties. The back-translation was then sent to a group of experts for evaluation. Each expert assessed all items of the original version of the instrument of translation and back translation and synthesis for all items except item 17, the three experts had agreed. After the expert analysis of the back-translation by the group of experts, the final version was sent to the author for approval of adaptations of some items to our reality. None of the items was modified regarding their understanding but adapted to the Brazilian reality. The author of the instrument accepted and authorized the changes. In the end, a pre-test was performed for assessment of the psychometric properties for the 24 items and the decomposition of the six most correlating factors, with a Chronbach’s alpha of 0.916. Conclusion:The study had a strong internal consistency and, therefore, high reliability of the scale. The cross-cultural adaptation maintained the psychometric properties of the original scale. Future studies can be performed in order to validate the instrument, study the impact of nursing counseling on smoking cessation, and identify which nursing activities are most effective in reducing smoking.